Dari Materialisme Ke Identitas: Transformasi Radikalisme Kelas Menengah Muda - Wasisto Raharjo Jati (Jurnal Studi Pemuda, 2016)
The terminology of radicalism had been accepted largery as physical expression aims to create violence and riots. Radicalism is understood as informal style to negotiate when formal politics unsuccessfully created resolution. The young middle class were categorized vulnerable groups which easily infiltrated within several of ideologies. However, it is important to be noted that radicalism is a way to make expression space for youth people. The role of social media altered characteristic of movement that become rigorious. By using both perspective namely new social movement dan resources mobilization, this article aimed to analyse great transformation on radicalism nowadays.